BROWNIES TEMPE SUBSTITUSI WORTEL MELALUI UJI ORGANOLEPTIK DAN ANALISA ZAT GIZI SEBAGAI ALTERNATIF MAKANAN SELINGAN PADA ANEMIA IBU HAMIL - Nurhamidah, Nurhamidah; Dwita Adfar, Tika (Ensiklopedia of Journal, 2024)
According to WHO, in developing countries, anemia in pregnant women is more often found in Africa and Southeast Asia, including Indonesia. The rate of anemia in Indonesia in pregnant women is still quite high. Tempe contains a variety of vitamins and iron that can be used to increase blood Hb cells. Tempe will be processed into brownies, which is a very popular food as a snack for anemia. The purpose of this study was to determine the average value of color, texture, aroma, and taste in brownies and to determine the best levels of iron and vitamin A for brownies. This study used a completely randomized design (CRD) 1 control and 3 treatments with 2 repetitions, organoleptic test. The method used is hedonic test with 25 panelists. The data was processed using the SPSS program with analysis of variance (ANOVA) at the 5% level. If there is a significant difference, then it is continued with the Duncan New Multiple Range Test (DNMRT) at a 5% significance level. Based on the research results of carrot substitution tempe brownies , the highest organoleptic test values were obtained, namely treatment D (tempe 25 g and carrots 75 g) and contained Vitamin A as much as 7.73% and contained FE as much as 2.7778 ppm. The results obtained from the research with the hedonic test of carrot substitution tempe brownies on color, aroma, texture, taste there are significant differences. Pregnant women who have anemia can consume tempeh brownies instead of carrots because they contain vitamin A and iron (Fe).Keywords: Anemia, Pregnant women, Tempeh, Carrots, Brownies